Respuesta :

9514 1404 393

Answer:

  multiply their coefficients, use the base with the sum of exponents

Step-by-step explanation:

The coefficients multiply. The base gets an exponent that is the sum of the exponents of the factors.

  (a·x^b)(c·x^d) = ac·x^(b+d)

_____

If you remember that an exponent is simply an indicator of the number of times the base is a factor, this should be fairly clear. The usual associative and commutative properties of multiplication apply.

Example

  5x^2 · 7x^3= 5·x·x·7·x·x·x

  = 5·7·x·x·x·x·x

  = (5·7)(x^(2+3))

  = 35x^5

ACCESS MORE